Integrative Human Resource Governance for Enhancing Coordination and Performance in Shipyard Industries of Batam - I Made Sondra Wijaya; Dimas Akmarul Putera; Roni Adi; M. Irvanni Bahri; M. Ansyar Bora (Goodwood Publishing, 2026)
Purpose: This study aims to explain how integrated Human Resource (HR) governance strengthens coordination mechanisms and improves organizational performance in the shipbuilding industry in Batam. Methodology: This study adopts a qualitative case study approach involving three major shipyard companies in Batam, Indonesia. Data were collected through in-depth interviews with nine key informants, including HR managers, operations heads and project supervisors. The data were analyzed thematically to identify the relationships between HR governance practices, coordination processes, and performance outcomes. Results: The study identified four key findings. First, integrated workforce planning aligns the labor allocation with the project timelines, thereby reducing delays and rework. Second, cross-functional coordination supported by shared HR governance frameworks improves communication across units, enabling faster decision making and problem solving. Third, structured training and competency development programs enhance workforce adaptability and improve technical accuracy. Fourth, integrated performance evaluation systems that combine individual and team-based indicators strengthen accountability and collaboration, resulting in improved productivity and organizational responsiveness. Conclusions: The findings show that integrated HR governance plays a vital role in strengthening coordination, improving organizational performance, and enhancing competitiveness through collaborative leadership and an open organizational culture. Limitations: This study is limited to three large shipyard companies in Batam; therefore, the findings may not fully represent practices across the broader maritime industry. Contributions: Theoretically, this study enriches the literature on integrated HR governance by providing empirical evidence from the shipbuilding sector. Practically, it provides guidance for managers and policymakers in developing adaptive, collaborative, and performance-oriented HR systems.